2022
DOI: 10.3390/antiox11020432
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with a Cocoa–Carob Blend, Alone or in Combination with Metformin, Attenuates Diabetic Cardiomyopathy, Cardiac Oxidative Stress and Inflammation in Zucker Diabetic Rats

Abstract: Diabetic cardiomyopathy (DCM) is one of the main causes of mortality among diabetic patients, with oxidative stress and inflammation major contributors to its development. Dietary flavonoids show strong antioxidant and anti-inflammatory activities, although their potential additive outcomes in combination with antidiabetic drugs have been scarcely explored. The present study investigates the cardioprotective effects of a cocoa–carob blend (CCB) diet, rich in flavonoids, alone or in combination with metformin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Bacterial strains were incubated in MRS broth supplemented with different final concentrations (2,4,8,16,32,64,128,256, 512 and 1024 µg/mL) of antibiotics for 24 h incubation at 37 • C, and assayed in triplicate in a microplate reader (OD at 610 nm) [29]. MICs (minimum inhibitory concentrations) were considered the lowest concentrations of antibiotics that could inhibit strain growth, which was used to evaluate the antibiotic resistance of selected strains.…”
Section: Antibiotic Resistance Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial strains were incubated in MRS broth supplemented with different final concentrations (2,4,8,16,32,64,128,256, 512 and 1024 µg/mL) of antibiotics for 24 h incubation at 37 • C, and assayed in triplicate in a microplate reader (OD at 610 nm) [29]. MICs (minimum inhibitory concentrations) were considered the lowest concentrations of antibiotics that could inhibit strain growth, which was used to evaluate the antibiotic resistance of selected strains.…”
Section: Antibiotic Resistance Assaymentioning
confidence: 99%
“…Oxidative stress is an excessive production of ROS, which can provoke the onset and progression of various diseases, including diabetes [ 16 ], cancer [ 17 ] and cardiovascular diseases [ 18 ], etc. Accumulating studies have suggested that intestinal flora metabolites may participate in the modulation of inflammation-related diseases through regulating oxidative stress [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Test group showed better biochemical test results, indicating possible potential of this powder in blood sugar control [42].…”
Section: Antidiabeticmentioning
confidence: 88%
“…Antidiabetic activity of Carob was extensively studied [38][39][40][41][42], especially in the context of insulin-resistance and D-Pinitol activity, which is the major insulin regulator in Carob [129]. But Carob contains other natural products that have insulin regulation, as well as other health promoting activities: phytosterols (Figure 7) [91].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed attenuated cardiac dysfunction, hypertrophy, and fibrosis compared with the control group. The proposed mechanisms include the downregulation of NOX and modulation of the cellular antioxidant defense system, of which sirtuin-1 and Nrf2 are part [ 65 ].…”
Section: Phytochemicals/phytonutrientsmentioning
confidence: 99%